Rectus femoris and vastus intermedius muscle asymmetries following ACL reconstruction - Fasih, Manal; Voskuil, Caleb; Rivas, Christopher; Lee, Bobby; Nadolny, Caitlin; Dietrich, Lindsey; Carr, Joshua (International Journal of Sports Medicine, 2025)
Anterior cruciate ligament reconstruction induces deleterious neuromuscular alterations. Musculoskeletal ultrasonography provides an accessible method to quantify muscle size and quality in patients with anterior cruciate ligament reconstruction who suffer from persistent skeletal muscle atrophy. This study compares rectus femoris and vastus intermedius muscle thicknesses and echo intensities using extended field-of-view ultrasonography in individuals with a history of anterior cruciate ligament reconstruction versus non-injured controls. Twenty-six individuals with previous anterior cruciate ligament reconstruction and 20 controls were participated in this study. Extended field-of-view ultrasonography was used to analyze the muscle thickness in the proximal, middle, and distal regions of the thigh, while the echo intensity was measured to assess the muscle quality. Findings indicate significant asymmetries in the muscle thickness (p<0.01 and ηp2=0.312) and echo intensity (p=0.024 and ηp2=0.111) for the anterior cruciate ligament reconstruction group, favoring the uninvolved leg, with no site-specific differences between groups. Results show muscle-specific size differences, with greater vastus intermedius muscle thickness than rectus femoris muscle thickness in controls (p<0.01 and d=0.609), but no difference between muscles in either leg of the anterior cruciate ligament reconstruction group (p>0.05 and d=0.094). Overall, these results highlight unique skeletal muscle changes between the biarticular rectus femoris and the monoarticular vastus intermedius following anterior cruciate ligament reconstruction, likely reflecting postoperative deficiencies in knee extensor function.
Keywords: arthroplasty; skeletal muscle; ultrasonography; ACLR; sports medicine